The Chief Scientist Office Cardiovascular and Pulmonary Imaging in SARS Coronavirus disease-19 (CISCO-19) study. Issue 14 (23rd July 2020) - Mangion, Kenneth; Morrow, Andrew; Bagot, Catherine; Bayes, Hannah; Blyth, Kevin G; Church, Colin; Corcoran, David; Delles, Christian; Gillespie, Lynsey; Grieve, Douglas; Ho, Antonia; Kean, Sharon; et al.
Abstract: Background: COVID-19 is typically a primary respiratory illness with multisystem involvement. The prevalence and clinical significance of cardiovascular and multisystem involvement in COVID-19 remain unclear. Methods: This is a prospective, observational, multicentre, longitudinal, cohort study with minimal selection criteria and a near-consecutive approach to screening. Patients who have received hospital care for COVID-19 will be enrolled within 28 days of discharge. Myocardial injury will be diagnosed according to the peak troponin I in relation to the upper reference limit (URL, 99th centile) (Abbott Architect troponin I assay; sex-specific URL, male: >34 ng/L; female: >16 ng/L). Multisystem, multimodality imaging will be undertaken during the convalescent phase at 28 days post-discharge (Visit 2). Imaging of the heart, lung, and kidneys will include multiparametric, stress perfusion, cardiovascular magnetic resonance imaging, and computed tomography coronary angiography. Health and well-being will be assessed in the longer term. The primary outcome is the proportion of patients with a diagnosis of myocardial inflammation. Conclusion: CISCO-19 will provide detailed insights into cardiovascular and multisystem involvement of COVID-19. Our study will inform the rationale and design of novel therapeutic and management strategies for affected patients. Clinical trial registration: ClinicalTrials.gov identifier NCT04403607.